#TITLE_ALTERNATIVE# - SUNANTIO (NIM 13003012), LEVINA
Indonesia as the second biggest crude palm oil (CPO) producer is predicted to be the biggest producer of CPO by 2010. Thus, this target has triggered the CPO industries. Conventionally, phases necessary to produce CPO can be differed into four major phases (i.e. pre-processing, oil extracting, oil clarification, and mud processing). Problems occurred nowadays is the time spent on oil clarification which is done conventionally. Therefore, a technique called membrane technology has been developed to shorten process. The lesser time needed, the lesser the production cost will be. And better yet, the production will be much faster. This research has two major phases. They are pre-treatment of CPO produced by vibrating screen unit and evaluation on clarification membrane performance. CPO pre-treatment was done by removing large size of insoluble impurities with centrifuged to lighten the work of the membrane. Performance of the membrane in CPO clarification process was evaluated through analysis on the fluxes value, percentage of insoluble impurities, and also water content of CPO that was being produced from each operational condition variation. Cross flow membrane filtration temperatures were varied from 40°C, 50°C, and 60°C; trans membrane pressures (TMP) used 1,5 bar 1,7 bar, and 2,2 bar; and the backflushing intervals for this research used 3, 5, and 7 minutes. The permeate quality which has reach the requirements in conventional clarification unit showed that hydrophobic microporous hollow fiber membrane could be used for clarification process in CPO industries. From the results also proved that operation temperatures, TMP, and backflushing intervals influenced the permeate fluxes.